The effect of mild electrical stimulation with heat shock on diabetic KKAy mice. Issue 1 (2016) - Kai, Yukari; Tsurekawa, Yu; Fukuda, Ryosuke; Omachi, Kohei; Piruzyan, Mariam; Okamoto, Yuka; Motomura, Keishi; Ann, Mary; Shuto, Tsuyoshi; Kondo, Tatsuya; Araki, Eiichi; Kai, Hirofumi
No abstract available